A AND D SURFACTAN PROTEINS IN LUNG IMMUNE SYSTEM - Linawati, Ni Made (Medicina; Vol 43 No 1 (2012): Januari 2012, 2013)
The surfactant associated proteins of  the lung are component of  lung innate immunity. Its functions in host defence is mediated by surfactant associated protein A and D. surfactant associated protein A and D are collectins familly, both synthesized and secreted by many cells in different parts of our body. (MEDICINA 2012;43:46-48).
Keywords: surfactant associated protein A, surfactant associated protein D, lung immunity